Simplifying plant gene silencing and genome editing logistics by a one‐Agrobacterium system for simultaneous delivery of multipartite virus vectors. Issue 7 (4th April 2022) - Aragonés, Verónica; Aliaga, Flavio; Pasin, Fabio; Daròs, José‐Antonio
Abstract: Viral vectors provide a quick and effective way to express exogenous sequences in eukaryotic cells and to engineer eukaryotic genomes through the delivery of CRISPR/Cas components. Here, we present JoinTRV, an improved vector system based on tobacco rattle virus (TRV) that simplifies gene silencing and genome editing logistics. Our system consists of two mini T‐DNA vectors from which TRV RNA1 (pLX‐TRV1) and an engineered version of TRV RNA2 (pLX‐TRV2) are expressed. The two vectors have compatible origins that allow their cotransformation and maintenance into a single Agrobacterium cell, as well as their simultaneous delivery to plants by a one‐ Agrobacterium /two‐vector approach. The JoinTRV vectors are substantially smaller than those of any known TRV vector system, and pLX‐TRV2 can be easily customized to express desired sequences by one‐step digestion‐ligation and homology‐based cloning. The system was successfully used in Nicotiana benthamiana for launching TRV infection, for recombinant protein production, as well as for robust virus‐induced gene silencing (VIGS) of endogenous transcripts using bacterial suspensions at low optical densities. JoinTRV‐mediated delivery of single‐guide RNAs in a Cas9 transgenic host allowed somatic cell editing efficiencies of ≈90%; editing events were heritable and >50% of the progeny seedlings showed mutations at the targeted loci. Graphical Abstract and Lay Summary: Viral vectors are powerful tools for exogenous sequence delivery in plant cells. In this study, JoinTRV is designed for simultaneous delivery of engineered tobacco rattle virus (TRV) RNA1 and RNA2 components from a single Agrobacterium cell in a 1‐strain/2‐vector system. JoinTRV allows flexible plant delivery of multi‐component viral vectors as well as overexpression of genes of interest (GOI), virus‐induced gene silencing (VIGS) and genome editing (VIGE).